Reciprocal Sex Partner Concurrency and STDs among Heterosexuals at High-Risk of HIV Infection - Neaigus, Alan (Springer US, 2012)
Inconsistent findings on the relationship of sex partner concurrency to infection with HIV and other sexually transmitted diseases (STDs) may result from differences in how sex partner concurrency is conceptualized. We examine the relationship of reciprocal sex partner concurrency (RSPC) to diagnosed STDs among heterosexuals. Heterosexually active adults (N = 717) were recruited for a cross-sectional study using respondent-driven sampling (RDS) from high-HIV-risk areas in New York City (NYC, 2006–2007) and interviewed about their sexual risk behaviors, number of sex partners, last sex partners, and STD diagnoses (prior 12 months). RSPC was when both the participant and her/his last sex partner had sex with other people during their sexual relationship. Odds ratios (OR), adjusted odds ratios (aOR), and 95 % confidence intervals (95%CI) were estimated by logistic regression. The sample was 52.4 % female, 74.3 % Black; median age was 40 years. RSPC was reported by 40.7 % and any STD diagnoses by 23.4 %. Any STDs was reported by 31.5 % of those reporting RSPC vs. 17.9 % of those who did not (OR = 2.11, 95%CI = 1.49–3.0). Any STDs was independently associated with RSPC (aOR = 1.54, 95%CI = 1.02–2.32), female gender (aOR = 2.15, 95%CI = 1.43–3.23), having more than three sex partners (aOR = 1.72, 95%CI = 1.13–2.63), and unprotected anal sex (aOR = 1.65, 95%CI = 1.12–2.42). Heterosexuals in high-HIV-risk neighborhoods in sexual partnerships that involve RSPC are at greater risk of STDs and, potentially, HIV. RSPC, in addition to sexual risk behaviors and the number of sex partners, may facilitate the heterosexual spread of HIV through STD cofactors and linkage into larger STD/HIV sexual transmission networks.